2019
DOI: 10.1007/978-3-030-32245-8_30
|View full text |Cite|
|
Sign up to set email alerts
|

Automatic Segmentation of Vestibular Schwannoma from T2-Weighted MRI by Deep Spatial Attention with Hardness-Weighted Loss

Abstract: Automatic segmentation of vestibular schwannoma (VS) tumors from magnetic resonance imaging (MRI) would facilitate efficient and accurate volume measurement to guide patient management and improve clinical workflow. The accuracy and robustness is challenged by low contrast, small target region and low through-plane resolution. We introduce a 2.5D convolutional neural network (CNN) able to exploit the different in-plane and through-plane resolutions encountered in standard of care imaging protocols. We use an a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 11 publications
1
47
0
Order By: Relevance
“…Then, to investigate the efficacy of deep supervision, we trained our model with different supervision strategies. Specifically, we compared training with supervision at: 1) only the final network output, 2) both the final output and the multi-scale features, and 3) the attentive maps instead of attentive features in an approach similar to [57].…”
Section: A Alternative Techniquesmentioning
confidence: 99%
“…Then, to investigate the efficacy of deep supervision, we trained our model with different supervision strategies. Specifically, we compared training with supervision at: 1) only the final network output, 2) both the final output and the multi-scale features, and 3) the attentive maps instead of attentive features in an approach similar to [57].…”
Section: A Alternative Techniquesmentioning
confidence: 99%
“…We have previously developed a novel artificial intelligence (AI) framework based on a 2.5D convolutional neural network (CNN) able to exploit the different in-plane and through-plane resolutions encountered in standard clinical imaging protocols 9,10 . In particular, we embedded a computational attention module to enable the CNN to focus on the small VS target and included a supervision on the attention map for more accurate segmentation.…”
Section: Background and Summarymentioning
confidence: 99%
“…A comparison between the 2.5D UNet on which our implementation is based and a 3D UNet as well as other baseline neural networks without attention module and/or hardness-weighting was published in, 9 showing improvements in Dice score of more than 3%.…”
Section: Technical Validationmentioning
confidence: 99%
“…In addition, studies have demonstrated that using multiparametric MR images improves detection for brain tumors with multiple subregions [14][15][16]. For VS tumor detection, Wang et al [17] and Shapey et al [18] demonstrated the feasibility of CNN and multiparametric MR images to the segmentation of VS lesions. Lee et al [19] improved VS lesion detection by treating multiparametric MR images from the same patient as different channels of the same image.…”
Section: Introductionmentioning
confidence: 99%